Development of Card Media Based on Yu Gi Oh Game To Increase Mathematical Literacy Skills of Islamic Elementary School Students - Muhammad Ilman Nafi'an; Sirojul Chikam; Aulia Rohmawati (CV. ULIL ALBAB CORP, 2024)
This research focuses on the use of mathematics teaching materials on fractions that are less interesting and less connect mathematics material with concrete situations and useful in students' lives. The purpose of this research is to create a product of Teaching Materials on Fraction Materials by using the Problem Card approach and linking it to the Context of the Yu Gi Oh Game which is not only scientifically valid but also easy to apply in practice. This research was conducted in grade II at Madrasah Ibtidaiyah Islamiyah Kumisik. This research is a type of development research that uses a customised development model of the ADDIE model. This model consists of 5 stages, namely: 1) Analyze stage, 2) design stage, 3) development stage, 4) implementation stage. Implementation stage. Data were collected through interviews and questionnaires. From the evaluation by experts, the validation scores obtained were 0.85 for learning experts, 0.84 for media experts, and 0.90 for material experts, with an average value reaching 0.88. Meanwhile, the results of the analysis of teacher practicality showed an average score of 0.90, and for student practicality, the average score was 0.87, 5) Evaluation Stage. Therefore, it can be concluded that the Teaching Materials for Fraction Materials Based on Problem Cards and Using the Context of the Yu Gi Oh Game have met the standards of validity and practical usability, making them suitable to be applied in the learning process regarding fraction materials.